High removal performance of dissolved oil from aqueous solution by sorption using fatty acid esterified pineapple leaves as novel sorbents - Cheu, S.C. (Royal Society of Chemistry, 2016)
This paper demonstrates the potential use of the lignocellulosic biomass of pineapple leaves (PALs) as an oil sorbent by mercerization and esterification with long chain fatty acids in order to enhance the surface hydrophobicity and thus the oil sorption capacity for the treatment of dissolved oil contaminated wastewater. The mercerized pineapple leaves (M-PALs) were esterified with lauric acid (LA) and stearic acid (SA) in pyridine-p-toluenesulfonyl chloride (Py-TsCl) solution to yield M-LA-PAL and M-SA-PAL sorbents, respectively, which were then characterized alongside the raw PAL (R-PAL) sorbent using scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), CHNS/O analysis and Brunauer-Emmett-Teller (BET) surface area analysis to study the changes of the surface morphology, functional groups, elemental composition and specific surface area of the sorbents. It was found that M-SA-PAL gave the highest sorption capacity (138.89 mg g-1) followed by M-LA-PAL (107.67 mg g-1) and R-PAL (35.59 mg g-1), which are generally lower than dispersed oil sorption capacities. The oil sorption process was found to be exothermic in nature. The data analysis indicated that the sorption process obeyed the Langmuir isotherm and pseudo-second order kinetic models with film diffusion as the rate limiting step, which is similar to some of the reported dispersed oil sorption results. The sorbent regeneration was repeated four times using isopropanol-water (1:1, v/v) solution as a desorbing agent and the sorption results were found to be comparable with the freshly prepared sorbent. Finally, the present findings indicate that a lignocellulosic biomass such as PAL could be a potential alternative sorbent precursor for oil removal from oil contaminated wastewaters. Â© 2016 The Royal Society of Chemistry.